HARGA DIRI, KREATIVITAS DAN KECERDASAN EMOSIONAL SISWA KELAS AKSELERASI, UNGGULAN DAN REGULER - Yosi Adilla; Sahat Saragih; Muhammad Farid (Jurnal Psikologi Tabularasa, 2011)
Abstract Self-esteem, creativity abd emotional intelligence ossessed in comparational quantitative research studernts through an accelerated program clusters, excelent, and regular. Research subjects were 171 students of Madrasah Tsanawiyah Negeri II Kediri. Researchers used SES to measure of self-esteem, C.O.R.E scale to measure creativity, and develop emotional intelligence scale. Data were analyzed with One Way ANOVA and Independent Sample t-test. Average self-esteem and creativity on classes of accelerated, excellent, and regular no different; Average of emotional intelligence on class of acceleration, excellent, and regular differ signficantly; Emotional intelligence on regular ctais is higher than accelereted and excellent class, Average of emotional intellengence on excellent grade is higher than acceleration; Students on accelerated class has the lowest emotional intelligence. Key words : Self-esteem, Creativity, Emotional Intelligence